The ‘black spot’ on the Crimea: venereal diseases in the Black Sea fleet in the 1920s - Hearne, Siobhan (Taylor & Francis, 2017)
This article examines how high command in the Soviet Red Navy responded to reportedly high levels of venereal diseases in the Black Sea fleet in the mid-1920s. Illness in the fleet posed a threat to national security, especially during the first unstable decade of the Soviet Union’s existence. Naval command and the municipal authorities of the Crimean Autonomous Soviet Socialist Republic (Crimean ASSR) targeted three main points for reform: the source of infection, those who became infected, and the urban space of Sevastopol. The majority of studies of venereal diseases in military populations have been situated within wartime, whereas this article explores the construction of disease during peacetime to interrogate how the naval and municipal authorities in the Black Sea justified intervention into the private, and intimate, lives of sailors and the wider population.